2017
DOI: 10.13031/trans.12239
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Irrigation Amount on Alfalfa Yield and Quality with a Center-Pivot System

Abstract: Abstract. Irrigation amount is one of the most important factors that need to be considered in the management of center-pivot irrigation systems for alfalfa producers. In 2014 and 2015, a field study was conducted at Saiwusu, Inner Mongolia, China. Three irrigation levels (100%, 80%, 60% ET) were used to evaluate the effects of irrigation amount on alfalfa yield and quality. For assessing the effects of water distribution variation of center-pivot systems on alfalfa yield and quality, the water application dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…supply less than optimum (deficit) irrigation (Li et al, 2017;Montoya et al, 2017;Fucang et al, 2015;Zafar et al, 2020). Massive output return of agricultural production can be achieved by maintaining environmental quality and efficiently managing inputs practising like irrigation scheduling and efficient use of fertilizer (Macintosh et al, 2019;Willy et al, 2019).…”
Section: Crop Yieldmentioning
confidence: 99%
“…supply less than optimum (deficit) irrigation (Li et al, 2017;Montoya et al, 2017;Fucang et al, 2015;Zafar et al, 2020). Massive output return of agricultural production can be achieved by maintaining environmental quality and efficiently managing inputs practising like irrigation scheduling and efficient use of fertilizer (Macintosh et al, 2019;Willy et al, 2019).…”
Section: Crop Yieldmentioning
confidence: 99%
“…Zhao et al (2017) found that available water-holding capacity (AWC) was an effective metric for delineating zones for variablerate irrigation, and that differences in AWC influenced corn and winter wheat yields and water productivity in an alluvial flood plain in China. Alfalfa yield and crop water-use efficiency in a semi-arid region of China had greater response to irrigation application prior to the first cutting and progressively less response to applications prior to second and third cuttings (Li, M. et al, 2017); irrigation also affected relative Table 1. Summary of modeling research published in 2017 and discussed herein.…”
Section: Crop Yields and Water Usementioning
confidence: 99%
“…The deep root system in alfalfa helps to address the runoff and deep percolation problems in semiarid regions. Alfalfa is also a good candidate crop for applying deficit irrigation due to its drought stress tolerance and partial tendency to offset yield reductions with high forage quality (Lindenmayer et al, 2008(Lindenmayer et al, , 2011Ismail and Almarshadi, 2013;Jafarian et al, 2016;Cavero et al, 2017;Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Irrigation management also has been explored for increasing alfalfa yield in semiarid subtropical environments. Most of the work in both semiarid and arid irrigated and higher precipitation areas has focused on the effects of in-season irrigation modifications (Tapia and Lugg, 1986;Hancock and Dougherty, 2006;Hanson et al, 2007;Malinowski et al, 2007;Lindenmayer et al, 2008Lindenmayer et al, , 2011Abd El-Mageed and Semida, 2015;Jafarian et al, 2016;Abd El-Mageed et al, 2017;Cavero et al, 2017;Li et al, 2017;Abd El-Mageed et al, 2018). Ottman et al (1996), in the desert southwestern USA, found that winter termination of irrigation was preferable to suboptimal summer irrigation.…”
Section: Introductionmentioning
confidence: 99%